STYLISTIC POTENTIAL OF LINGUISTIC AND SPEECH UNITS IN THE SPEECH ACT OF REPROACH - Abduqodirova Madina Abduqayum qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation. This article analyzes the stylistic potential of linguistic and speech units in the speech act of reproach. Expressions of dissatisfaction, criticism, or objection are conveyed through various stylistic means in speech. The article examines the lexical, grammatical, and pragmatic features of these means and illustrates their use in reproach through concrete examples. Special attention is also given to the comparative analysis of stylistic features of reproach in Uzbek, Russian, and English languages.